Optimal paediatric cardiac services in South Africa – what do we need? - Hoosen, E.G.M.; Cilliers, A.M.; Hugo-Hamman, C.T.; Brown, S.C.; Harrisberg, J.R.; Takawira, F.F.; Govendrageloo, K.; Lawrenson, J.; Hewitson, J. (SA Heart Journal, 2017)
Most children with congenital heart disease have a good outcome if treated appropriately, however the majority of children with heart disease in South Africa do not receive appropriate care. This is related to serious deficiencies in the mechanisms and training for early detection as well as a major shortage of skilled personnel to care for these children at all levels. Most public sector hospitals are unable to cope with the number of patients requiring surgery, mainly due to inadequate theatre time allocation and intensive care facilities. Key interventions to address these deficiencies include: 1. Strategies to improve both the training and the retention of all professionals involved in the care of congenital heart disease. 2. Programmes to increase awareness of both congenital and acquired heart disease in children among health care personnel. 3. Ensuring appropriate infrastructure and equipment designed for children with congenital heart disease are available. 4. Development of congenital heart surgery as an independent subspecialty with dedicated resources and personnel. 5. Dedicated intensive care facilities for paediatric heart surgery. In addition, development of appropriate patterns of referral, stimulation of research and positive private-public partnerships are all necessary to ensure that appropriate care is delivered.